2016
DOI: 10.3390/su8060571
|View full text |Cite
|
Sign up to set email alerts
|

Residents’ Environmental Conservation Behaviors at Tourist Sites: Broadening the Norm Activation Framework by Adopting Environment Attachment

Abstract: Understanding the factors that affect residents' environmental conservation behaviors help in managing the environment of tourist sites. This research provides an integrative understanding of how residents near tourist sites form their environmental conservation behaviors by merging the norm-activation model and cognitive-affective model into one theoretical framework. Results of the structural analysis from a sample of 642 residents showed that this study's proposed composite model includes a satisfactory lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 49 publications
(43 reference statements)
0
13
1
Order By: Relevance
“…In this research, PEB refers to the actions taken by individuals or groups that promote or result in the sustainable development of natural resources [42]. Residents can be strategic participants in the construction of a destination's ecological image, and their PEB may strongly bond with sustainable destination development [5].…”
Section: Eagly and Chaikenmentioning
confidence: 99%
See 2 more Smart Citations
“…In this research, PEB refers to the actions taken by individuals or groups that promote or result in the sustainable development of natural resources [42]. Residents can be strategic participants in the construction of a destination's ecological image, and their PEB may strongly bond with sustainable destination development [5].…”
Section: Eagly and Chaikenmentioning
confidence: 99%
“…Residents are important stakeholders in tourism development and have the strongest bonds with destinations because their livelihoods and well-being are closely linked to the quality of the environment. Moreover, residents' behaviors and activities have a direct, comprehensive, and deep impact on the quality of the destination environment [5]. Therefore, fostering residents' pro-environmental behavior (hereinafter named as PEB) can be one of the foundations for sustainable destination development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have mostly focused on exploring tourists' environmental behaviors [12,[16][17][18][19][20][21][22]. Some research has explored residents' environmental behaviors [23,24]. However, investigations to determine the environmental behaviors of tourism employees are scarce.…”
Section: Environmentally Responsible Behaviors and Sustainable Tourismmentioning
confidence: 99%
“…Some previous related studies have focused on community involvement and relationships between a protected area and the community, and it has been concluded that participatory approaches and collaboration can promote positive relationships between management agencies and local people, thereby supporting protection of the reserve [9][10][11]. Moreover, several studies have shown that local attitudes are a key factor that influences relationships between communities and protected areas [12][13][14][15][16][17]. From a review of 105 published documents focusing on wildlife conservation, community involvement and protected area-community relationships, it emerged that relationships are mostly influenced by attitudes [18].…”
Section: Literature Reviewmentioning
confidence: 99%